Climate change and forests emerging policy and market opportunities - Streck, Charlotte (Chatham House ; Brookings Institution Press, 2008)
"Frames forestry activities within climate-change policy context. Analyzes the operation and efficacy of market-based mechanisms for forest conservation and climate change. Explores voluntary schemes for carbon crediting, provides an overview of carbon accounting best practices, and presents tools for future sequestration and offset programs. Concludes with options for slowing deforestation"--Provided by publisher.